Anisotropic moisture erosion of CH3NH3PbI3 single crystals. Issue 6 (18th January 2017) - Lv, Qianrui; He, Wenhui; Lian, Zhipeng; Ding, Jie; Li, Qiang; Yan, Qingfeng
Abstract : The anisotropy of moisture erosion was observed in CH3 NH3 PbI3 single crystals. Abstract : The anisotropy of moisture erosion was observed in CH3 NH3 PbI3 single crystals. When exposed to moisture, the (001) facet exhibited greater sensitivity to water molecules and showed a faster erosion rate compared to the (100) facet and (112) facet. Structural and chemical origins responsible for anisotropic moisture erosion were elucidated.